Smart Drip Using Arduino Microcontroller - Ajayan, Amal; Sheeja Kumari, V; Rahim, Fathima Abdul; Sooraj , S (International Journal of Computer Sciences and Engineering, 2019)
During recent years due to the technological advancements many sophisticated techniques has been evolved for assuring fast recovery of the patients in hospitals. For good patient care in hospitals, assessment and management of patient’s fluid in the drip is the most fundamental thing required. All most in all hospital, an assist/nurse is responsible for monitoring the fluid level continuously. But in the government hospitals due to the unavailability of enough number of nurses, observing this fluid is a great headache to the hospitals. Our smart drip using Arduino microcontroller will overcome the complications like infiltration, hematoma, air embolism, blood backup in tubing, extra vascular Injection, Intra-arterial Injection etc. It will detect the emptying of drip bag with the help of Ultrasonic sensor. To overcome this critical situation, we develop a smart drip using arduino with automatic alerting and indicating system is proposed where Ultrasonic sensor is used as a level sensor. Whenever the fluid becomes low, it will send an alert message to the nurse rooms and also nurses can monitor the LIVE level graph in their computer. This technology reduces the work of the nurse rather than keep on looking of an IV Fluid system. one of the best advantages of our project is that the ease interface with users that functionally can be managed by means of an alert message.